TaMYB29: A Novel R2R3-MYB Transcription Factor Involved in Wheat Defense Against Stripe Rust - Zhu, Xiaoxu; Li, Xiang; He, Qi; Guo, Dongxiao; Liu, Caiqi; Cao, Junying; Wu, Zhongyi; Kang, Zhensheng; Wang, Xiaojing (Frontiers in Plant Science, 2021)
Members of the R2R3-MYB transcription factor superfamily have been implicated in plant development, improved disease resistance, and defense responses to several types of stresses. To study the function of TaMYB29 transcription factor—a member of the R2R3-MYB superfamily—in response to an avirulent race of stripe rust pathogen, Puccinia striiformis f. sp. tritici (Pst), we identified and cloned the TaMYB29 gene from wheat cultivar (cv.) AvS+Yr10 following infection with Pst. The TaMYB29 protein, comprising 261 amino acids, contains two highly conserved MYB domains. We first showed that TaMYB29 is a transcription factor, whose transcriptional levels are significantly induced by salicylic acid (SA), abscisic acid (ABA), jasmonic acid (JA), ethylene (ET), and Pst. The results showed that TaMYB29 is involved in the wheat response to stipe rust. The overexpression of the TaMYB29 gene resulted in the accumulation of reactive oxygen species (ROS) and pathogen-independent cell death in Nicotiana benthamiana leaves. The silencing of TaMYB29 gene in wheat cv. AvS+Yr10, containing the stripe rust resistance gene Yr10, promoted hyphae growth, significantly downregulated the expression of pathogenesis-related (PR) genes, and substantially reduced the wheat resistance to Pst compared with the non-silenced control. In addition, the accumulation of hydrogen peroxide (H2O2) significantly decreased, and the activity of catalase, an enzyme required for H2O2 scavenging, was elevated. Altogether, TaMYB29 positively regulates the defense response against stripe rust in wheat AvS+Yr10 by enhancing H2O2 accumulation, PR gene expression, and SA signaling pathway-induced cell death. These results provide new insights into the contribution of TaMYB29 to the defense response against rust pathogens in wheat.